Repair of Pars Interarticularis Defect Utilizing a Pedicle and Laminar Screw Construct: A Technique Discussion and Case Series. Issue 1 (17th March 2021) - Snowden, Ryan; Sasso, Rick
Abstract : Introduction: Lumbar isthmic spondylolysis is a common disorder in young adults and adolescents. Following failure of nonoperative measures, multiple nonfusion techniques have been described to repair the spondylotic defect with varying results. Recently a new pedicle screw-laminar screw construct has been described and found comparable to other pedicle screw constructs in biomechanical testing. We describe the use of the pedicle screw-lamina screw constructs using image guidance and 3-dimensional imaging in the surgical management of isthmic spondylolysis. We also present a case series of patients undergoing treatment of isthmic spondylolysis. All patients undergoing pedicle screw-laminar screw pars repair construct from 2012 to 2017 by the senior author. Materials and Methods: All patients undergoing pedicle screw-laminar screw pars repair by the senior author from 2012 to 2017 were included. Patients were excluded for spondylolisthesis, disc degeneration at the level of spondylolysis, advanced age (>25), evidence of nerve root compression or significant signs of degenerative osteoarthritis. All patients failed a standardized course of nonoperative treatment before surgery. Patients were followed until full, pain-free activity had resumed. Six patients successfully underwent pedicle screw-laminar screw pars repair using intraoperative computed tomography guidance. There were no intraoperative or postoperative complications. All patients returned to full athletic activity at an average of 5.17 months. Final radiographs showed complete or near complete resolution of the defect in all cases. We are the first to describe the use of the pedicle screw-lamina screw constructs using image guidance and 3-dimensional imaging in the surgical management of isthmic spondylolisthesis in a clinical situation. The combination of pedicle screw and laminar screw provides a construct with robust fixation while allowing for ample bone grafting surface area. Furthermore, the utilization of intraoperative navigations provides an added measure of safety when placing both screws.